Building students' loyalty through superior university entities - Mahyuddin, Nafiza; Saad, Mazni; Wan Mohamad, Wan Nurul Fatimah; Ahmad, Aznita; Ong, Mohd Hanafi Azman (Malaysian Journal of Consumer and Family Economics (MACFEA), 2019)
This study expands a previous qualitative investigation of students’ experience of existing entities in higher education institutions (HEIs) of Malaysia. We specifically investigated how experience impacted students’ loyalty which eventually drove them to return to the same university for further studies. The Structural Equation Model with Partial Least Square (PLS-SEM) was done on a selected group of 200 undergraduates from these institutions. The findings illustrated the top three reasons that positively and significantly influenced their academic progression at the same university as Campus Infrastructure, Support System, and Teaching Quality. The study therefore concludes that if the average level of these three entities were good, then the level of Student Loyalty would also excel accordingly. The study highlights the need for HEIs to enhance their reputation by continuously improving and upgrading these identified entities to attract the university’s main stakeholders to come back for more quality learning experience.